Pengaruh Social Media Marketing Tiktok dan Kualitas Produk terhadap Keputusan Pembelian Produk Camille Beauty - Permatasari, Aulia Nur Indah; Hidayat, Agus Maolana (Jurnal Informatika Ekonomi Bisnis, 2023)
Currently, the trend of the Indonesian cosmetic industry is growing quite rapidly, especially in the skin care sector, so that competition in the skincare sector is becoming very tight. continue to increase. Camille Beauty is a beauty production company founded in 2018 and is one of the recommended products. Using Tiktok as a social media marketing platform to promote products sold to attract consumers to decide to buy Camille Beauty products. The purpose of this research was to find out and analyze how Tiktok's Social Media Marketing and Camille Beauty's Product Quality, to find out the Purchase Decision on Camille Beauty's Products, and to find out the Effect of Tiktok's Social Media and Product Quality on Camille Beauty's Purchase Decisions. This type of research is a quantitative method and uses descriptive data analysis. Sampling using non-probability sampling method. A total of 100 respondents. The data analysis technique used in this study is multiple linear regression analysis using IBM SPSS Statistics 26 software. The results obtained based on this research are that the social media marketing platform TikTok has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions, and social media marketing on the tiktok platform and product quality have a significant effect on purchasing decisions.